Close, but not too close: Landmarks and their influence on housing values. (March 2017) - Zawadzki, Stephanie J.; Mainzer, Stephen; McLaughlin, Rae Anne; Luloff, A.E.
Highlights: We modeled the influences of land use and sociodemographic factors on residential property value in a college town. Unexpectedly, proximity to open space and a community landmark do not significantly influence residential value. Also unexpectedly, proximity to the college campus (the town's primary employment center) decreases residential value. The results of the model are consistent at a second expanded (borough-wide) study area. These findings are contrary to the current literature and suggest that college towns may require a unique approach. Abstract: The college town of State College, PA, USA is home to The Pennsylvania State University (PSU) and its many facilities. Our initial research interest was to understand the influence of the newly developed Arboretum at Penn State (APSU) on nearby housing values in State College over time. Current sales transaction data were gathered and a pooled cross-sectional regression analysis approach utilized. Contrary to the literature, our findings suggest proximity to APSU, as well as three other nearby open spaces, had no significant influence on nearby homes. Further, proximity to PSU's main campus was negatively associated with housing values. Neither of these patterns varied over time. To further explore these results, the study area was expanded beyond the neighborhoods most proximate to APSU to the balance of the borough. These results replicated our earlier findings, confirming that living close to PSU's campus is negatively associated with housing values community-wide. These findings disconfirm the common practical assumption that the State College market places a premium on proximity to the town's major employment center (PSU campus) and a significant local landmark (APSU). Housing markets in similar college towns may not reflect typical residential areas and may require alternative evaluation considerations.